Monitoring Umur Padi berdasarkan Data Sensor Warna dengan menggunakan Protokol MQTT - Abdul Khafid; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Indonesia is an agricultural country known to the world as a rice producer. However, it is very unfortunate that this cannot meet the national rice needs which require Indonesia to import rice from other countries. One reason is the selection of rice harvest times by farmers. Based on these problems, there is a need for a system to help farmers calculate the age of paddy. This research utilizes NodeMCU V3, IC TCS3200 color sensor, Arduino IDE software and MQTT protocol to be assembled into a system. After several types of testing, it can be seen that this system can detect colors precisely as many as 13 times out of 20 attempts. In testing the reliability of data transmission carried out 20 times, all data totaling 10 data from the MQTT server to the serial monitor and the MQTT dashboard application were successfully sent and received as a whole without missing a single one. This means that the accuracy of delivery reaches 100% from 20 trials. In the experiment counting the delivery time that has been done as much as 20 times obtained the average delivery time is only 1.35 seconds.